A Novel miRNA From Egg-Derived Exosomes of Schistosoma japonicum Promotes Liver Fibrosis in Murine Schistosomiasis - Wang, Yiluo; Gong, Wenci; Zhou, Hao; Hu, Yuan; Wang, Lan; Shen, Yujuan; Yu, Guoying; Cao, Jianping (Frontiers in Immunology, 2022)
Schistosomiasis caused by Schistosoma japonicum is a serious public health problem in China. Granuloma and hepatic fibrosis are the main pathological features of schistosomiasis japonica. The role and mechanism of egg-derived exosomes of S. japonicum in liver fibrosis remain unclear. In this study, we found that egg-derived exosomes of S. japonicum carry a new type of microRNA (miRNA-33). In vitro, this novel miRNA upregulated the expression of smooth muscle actin (α-SMA) and collagen 1 α1 (Col 1 α1) in the human hepatic stellate cell (LX-2) line at both mRNA and protein levels. In vivo, this novel miRNA was upregulated in the serum of infected mice, and when injected into mice through the tail vein using miRNA agomir, α-SMA, Col 1 α1, and Col 3 α1 were upregulated in liver tissue at both mRNA and protein levels. In addition, this novel miRNA downregulated the expression of α-SMA and Col 1 α1 in liver tissue at mRNA and protein levels in mice infected with S. japonicum and treated with miRNA antagomir. The novel miRNA-33 upregulated TGF-β Receptor I (TGF-β RI) at both mRNA and protein levels in LX-2 cells. Our results suggest that this novel miRNA from egg-derived exosomes of S. japonicum can promote liver fibrosis in the host in a cross-species manner, and the degree of fibrosis can be decreased by inhibiting the expression of this miRNA.